Attacking Strategies That Lead to Goal Scoring Opportunities in High Level Women's Football - Mara, J. K.; Wheeler, K. W.; Lyons, K. (International Journal of Sports Science and Coaching, 2012)
This study identified the attacking strategies that lead to goal scoring opportunities in women's football (soccer). All regulär season games (n = 34) of the 2010/2011 W-League football competition were coded using performance analysis. Variables described the attacking strategies employed by teams and their association with goal scoring. It was shown that 24% (p < .001) of goals were the result of a cross (a distribution made from a wide area to a central area in front of goal). Further analysis demonstrated that 26% of corner kicks resulted in a shot at goal (p < .001). It was concluded that attacking through the wide areas of the field followed by a cross into a central zone inside the 18-yard box was the most effective strategy for creating goal scoring opportunities in women's football.